Young mothers' infant care sleep practices and factors which influence their practice choice : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology (Health Psychology endorsement) at Massey University, Palmerston North, New Zealand - Cronin, Tracey Marie (Massey University, 2014)
New Zealand has one of the highest Sudden Unexpected Death in Infancy (SUDI) rates in the industrialised world. Young Maternal Age (YMA) has been posited as a strong risk factor for SUDI. Little is known of the decision-making processes of young mothers which may contribute to the higher levels of risk. This study enquired into the experiences of young mothers with regard to their infant care sleeping practices. Through the use of Thematic Analysis (TA) it researched as to whether there were patterns in these mothers’ talk of their experiences, and then sought to understand the ways they constructed their practice choices, in order to provide explanation and understanding of the complex social environments in which these mothers must survive and how these may contribute to the overall statistics. Eleven young mothers were interviewed in semi-structured interviews. Five themes arose from the data: Needs of the Baby; Needs of the Mother; Baby’s Wishes; Mother’s Instinct or a Natural Ability; and, Non-compliance – Incognizant or Purposeful Action. Through analysis of the themes, it became clear that the social milieu of which these mothers are a part, has tended to influence their practice choices. However, one surprising discovery was how little their decision-making appeared to differ from that of other western parenting groups. What has been borne of the societal influences and attitudes toward this group is the unexpectedly comforting find that these mothers, despite their age, are resilient, resourceful, insightful young women who, like others, want nothing but the best for their infants. Implications of this work for practice, policy and research are discussed, and future recommendations made which make use of the resourcefulness of young mothers such as those in the present study. This group deserves the right to society’s respect, acceptance and, above all, support, which will enable them to be the valued, contributing members of society that they so rightfully deserve to be – as mothers, as women, and as an equal!
Keywords: Young mothers, New Zealand; Infant sleep practices; Sleeping practices